2015
DOI: 10.1093/gji/ggv121
|View full text |Cite
|
Sign up to set email alerts
|

Advances in GPR data acquisition and analysis for archaeology

Abstract: The primary objective of this study is to evaluate the applicability and the effectiveness of ground-penetrating radar (GPR) to identify a thin burnt soil layer, buried more than 2 m below the topographic surface at the Liangzhu Site, in Southeastern China. The site was chosen for its relatively challenging conditions of GPR techniques due to electrical conductivity and to the presence of peach tree roots that produced scattering. We completed the data acquisition by using 100 and 200 MHz antennas in TE and TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…The present work demonstrates that a proper combination of data acquisition and processing analysis techniques for both GPR [Zhao et al, 2015] and seismic can overcome the limits of standard GPR and seismic techniques and successfully image low-contrast and thin cultural targets such as contacts between clayey soils and rammed sandy soils, which are subsurface conditions frequently met at prehistoric sites.…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…The present work demonstrates that a proper combination of data acquisition and processing analysis techniques for both GPR [Zhao et al, 2015] and seismic can overcome the limits of standard GPR and seismic techniques and successfully image low-contrast and thin cultural targets such as contacts between clayey soils and rammed sandy soils, which are subsurface conditions frequently met at prehistoric sites.…”
mentioning
confidence: 92%
“…The study area is on top of an artificial hill, making the water level deeper, we were able to drill 2,4 m going through the thin layer as shown in Fig. 6, we choose the place of drilling on the point that crosses our seismic survey line with the attribute technique of GPR survey line by Zhao [Zhao et al, 2015], to be used for comparing our result with GPR results as shown in Fig. 7.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Ground Penetrating Radar (GPR) is a widely used method to investigate the underground archaeological and geological structures [3], [17]. The use of GPR in researches and applications has recently been increasing, because it can explore and detect the underground structures quickly and accurately.…”
Section: Introductionmentioning
confidence: 99%